Volunteering among youth with disabilities: a population-based study. Issue 1 (2nd January 2023) - Casseus, Myriam; Cheng, JenFu; Cooney, James M.
Abstract: Purpose: The benefits of volunteering among youth are well documented. However, research is limited on volunteering among youth with disabilities. This study examined prevalence and associations of volunteering among youth with disabilities. Methods: We analyzed data from the 2016–2018 National Survey of Children's Health ( n = 42 204). Prevalence estimates were calculated for sociodemographic and household factors, volunteering, and functional limitations. Bivariate and multivariable associations between participation in volunteering activities and variables of interest were assessed. Results: Youth with disabilities had lower prevalence of volunteering compared to youth without disabilities (48.4% vs. 55.6%). Youth with hearing and vision impairments had the lowest prevalence of volunteering (2.1% and 2.5%, respectively). Correlates of volunteering included health status (adjusted odds ratios (aOR)=1.81; 95% confidence interval (CI) 1.13–2.91), sex, and age. Conclusions: Our study found low prevalence of volunteering among youth with disabilities. Since youth with disabilities face unique barriers to social inclusion, it is important to identify and reduce the barriers to participation among this group. Volunteer opportunities in the community should be designed to be both environmentally and programmatically accessible to youth with disabilities. These efforts should include accommodations and other support so that participants can fully experience all of the benefits of volunteering. Implications for rehabilitation: Our multiyear nationally representative study found low prevalence of volunteering among youth with disabilities, particularly those with hearing and vision impairments. Since youth with disabilities face unique barriers to social inclusion, it is important to identify and reduce the barriers to participation among this group. Our findings support the need for environmentally and programmatically accessible volunteering opportunities for youth with disabilities. These efforts should include accommodations and other support so that participants can fully experience all of the benefits of volunteering.